Analisis Limbah Budidaya Ikan Patin (Pangasius Pangasius) Sistem Resirkulasi Terhadap Pertumbuhan Cacing Sutra (Tubifex sp) - Suharun Martudi; Firman Firman; Endang Srilestari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
The purpose of this research is to know the effect of biofloc and intensive Patin culture cultivation using recirculation system to growth of silk worm (Tubifex sp). The study was conducted for 70 days at the laboratory of Faculty of Agriculture Universitas Prof.Dr.Hazairin, SH, using a complete randomized design (RAL) with 2 (two) Treatments ,, 6 (six) replications. Using the C / N ratio of 15, consisting of: Treatment A = biofloc Patin cultivation waste, B = intensive Patin intensive system waste.. The results showed that: Tubifex sp cultivation (Tubifex sp) is best in the treatment of cultivation with biofloc system. For the average biomass weight of 0.105 gr / cmÂ² and the total number of individuals is 671,67 head / cmÂ². Biodiversity cultivation of biofloc system is also good for increasing the number of individuals compared to intensive system cultivation waste. For tubifex sp culture should use fish culture cultivation system bioflok